PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 022 RANTAU PANJANG KIRI KECAMATAN KUBU - Riadi '; Zulkifli '; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research is the process of learning andteaching fourth grade elementary school of 022 Rantau Panjang Left Kubudistrict in social studies are still didomonasi by the teacher so that studentsbecome passive, as well as materials provided by the teacher and the learningoutcomes are not satisfactory with an average value KKM below. This study aimsto determine the effect of quantum teaching learning models, both individuallyand on learning outcomes classical fourth grade students in social studieselementary school of 022 Rantau Panjang Left Kubu district. This study wasconducted on 25 students. Data were collected through observation using theobservation sheet to the data model of Quantum Teaching learning through UAS Iand UAS II for learning outcomes data. The results of the students increased inthe first cycle compared to prior to the action, while the improvement of learningoutcomes that occurred before and after the PTK held the first cycle an increaseof 28% in the first cycle is completed students were 17 to 68% completeness.While on the second cycle there was an increase of 20% with a completeness of88% of the 25 students. Then there is the difference in improvement between thefirst cycle and second cycle by 20%. While the activities of the students at the firstmeeting of the first cycle of 37.5%, the second meeting of 58.33% and the secondcycle at the first meeting at 70.83%, 91.66% for the second meeting. So, betweenthe first cycle and second cycle an increase of 33.32%. From the research anddiscussion as it has been described above that the use of Quantum Teachinglearning model is correct then the activities and outcomes of student learning isenhanced and better. This information proved that the hypothesis which says:With Application of Quantum Teaching Learning Model can improve learningoutcomes IPS Elementary School fourth grade students Rantau Panjang 022 LeftKubu district.Keywords: Quantum Teaching, IPS Learning Outcomes2PENERAPAN MODEL